Fox Wars and the Fur Empire: French and Native Campaigns against the Fox in the Great Lakes Region: 1701-1712 - Anklam, Oliver (My University, 2014)
At the turn of the 18th century King Louis XIV of France ordered a reduction of trading posts throughout North America and narrowed the locations to New Orleans, St. Louis, Chicago, and Detroit. Detroit served as the base of settlement for thousands of natives, including eventually the Fox and their Mesquakie allies. Shortly thereafter fighting broke out among natives and France was caught in the crossfire. The goal of New France was to sustain a relationship with the natives in order to engage in trade. However, France is forced to choose between aiding the Fox or their enemies. French officials became embroiled in hostile Indian politics that left the leadership with little choice but to aid in the elimination of the Fox instead of losing the powerful Native allies who threatened violence for any hospitality given to the Fox or their allies; French officials chose the former. French correspondence of the war serves as the main research base for this paper, along with the works of several credited historians.
Keywords: Fox Wars; Fox; Fur Trade; North American Fur Trade